Collaborative Governance Model on Agricultural Business in Banten, Indonesia - Hikmawan, M Dian; Hamid, Abdul; Nurrohman, Bayu; Ramadhan, Gilang; Mayrudin, Yeby Ma’asan (Jurnal Transformative, 2020)
One of the problems that become a threat to food security in Indonesia is agricultural degeneration. Recently, to perceive the food security issues is how collaborative governance works and how many actors engage to create food security. the problematic issue is the function of agricultural land occurs in the form of changes in the use of agricultural land into commercial lands such as housing, industrial areas, business, and trade centers. This research tries to elaborate on farming in Banten-Indonesia. Jawara Farm is one of the agriculture business models in Banten who drove by young people of Banten. This model business very interesting for alternatives in regeneration and business model in farming especially in Banten. Using qualitative methods and Collaborative governance approach, this research looking forward to the model of young farmers in Banten as a model in collaborative governance. This research found several challenges about the collaboration model between the young farmers, the government, and the private sector.